A Study on improve the Power System Stability by using the Load Following of the Nuclear Power Generator Control - Lee, Hyun-Chul; Roh, Young-Gi; Jung, Byoung-Jo (International Journal of Engineering and Technology, 2026)
Background/Objectives: This study is to improve the power system stability on the load following ability by using the governor control in the nuclear power generator. Methods/Statistical analysis: The control method has been the speed droop of the governor which is changed at a certain rate within the allowable range of the standard. The evaluation was applied the N-2 generator contingency and simulated the frequency fluctuation limit. The simulation results, it is possible to reduce the frequency drop width and obtain more economical results than operating the amphibious power generation for the purposed of setting the conventional governor infinite droop. Findings: The power capacity has increased due to the high growth of power demand in the power system. The power system was necessary that it has estimated the reasonable power reserve capacity for meeting the reliable supply power. The operating power reserve was calculated as difference between available power and operating power of the power supply generators. So, the power system is needed to secure the reserve power of generators control method. The generators weren’t shown same influence in the power system. However, it was operated the constant output of the nuclear generator power on account of the stability in the nations of the operating nuclear power system. In this paper, the power system reserve capacity was calculated by analyzing the load capacity and power reserve rate. Improvements/Applications: It is operating method that could be calculating the appropriate level of power reserve to apply economic feasibly and stability in the power system.